Pendampingan Pengelolaan Bank Sampah di Desa Larangan Kecamatan Candi Dalam Mendukung Program Sidoarjo Bersih dan Hijau melalui Pendekatan Triple Helix - Abdul Fatah Fanani; Diela Novelia; Muhammad Ichwan; Wahyu Astutik (LPPM Universitas Yudharta Pasuruan, 2021)
This article is the result of implementing community service assistance in managing the Berkah Berseri waste bank in Larangan village, Candi sub-district, Sidoarjo district. The main focus of the community service program carried out by the STIA Panglima Sudirman service team is on assisting Waste Bank activities using a triple helix model approach. The purpose of this activity is to encourage the realization of public awareness in waste management. the action research method used in the implementation of this community service program. The strategy used is to build a triple helix network model, which involves universities, industry, and the government. The result of this service program is the establishment of consolidation between communal waste banks in each RT/RW with the main waste bank at the village level. Cooperation with third parties, universities, industry and the government can be well established.